The Type of Fat in the Diet Influences the Behavior and the Relationship Between Cystinyl and Alanyl Aminopeptidase Activities in Frontal Cortex, Liver, and Plasma - Segarra, Ana Belén; Prieto, Isabel; Banegas, Inmaculada; Martínez-Cañamero, Magdalena; de Gasparo, Marc; Vanderheyden, Patrick; Zorad, Stefan; Ramírez-Sánchez, Manuel (Frontiers in Molecular Biosciences, 2020)
Insulin-regulated aminopeptidase (IRAP, cystinyl aminopeptidase, CysAP) and aminopeptidase M (alanyl aminopeptidase, AlaAP) are closely related enzymes involved in cognitive, metabolic and cardiovascular functions. These functions may be modulated by the type of fat used in the diet. In order to analyze a possible coordinated response of both enzymes we determined simultaneously their activities in frontal cortex, liver and plasma of adult male rats fed diets enriched with fats differing in their percentages of saturated, mono or polyunsaturated fatty acids such as sesame, sunflower, fish, olive, Iberian lard and coconut. The systolic blood pressure, food intake, body and liver weight as well as glucose and total cholesterol levels in plasma were measured. The type of fat in the diet influences the enzymatic activities depending on the enzyme and its location. These results suggest cognitive improvement properties for diets with predominance of polyunsaturated fatty acids. Physiological parameters such as systolic blood pressure, food intake and biochemical factors such as cholesterol and glucose in plasma were also modified depending on the type of diet, supporting beneficial properties for diets rich in mono and polyunsaturated fatty acids. Inter-tissue correlations between the analyzed parameters were also modified depending on the type of diet. If the type of fat used in the diet modifies the behavior and relationship between CysAP and AlaAP in and between frontal cortex, liver and plasma, the functions in which they are involved could also be modified.